Infraestrutura de mobilidade urbana e sua articulação com a drenagem sustentável - Talita Montagna; Rafaela Vieira (Confins)
The construction of the urban space tends to produce an impermeable cover on the ground that hampers rainwater infiltration. Therefore, drainage infrastructure should compensate. By blocking rainwater infiltration in the soil, surface runoff is increased and, consequently, the threats of inundation, flooding and flash flood, triggered by hydrological events, are potentiated. However, it is possible to promote the integration of basic infrastructure of a city, enhancing it. As an example, there is the use of non-motorized urban mobility infrastructure, such as sidewalk and bicycle lane for the application of sustainable urban drainage techniques. The objective of this study is to identify the type and extent of the coverings of public spaces that support the non-motorized mobility present in the lower section of the da Velha river basin in the city of Blumenau, state of Santa Catarina, Brazil, in order to evaluate the composition of these areas. A case study with a qualitative-quantitative nature was carried out. A total of 218,816.77 m² of structure was quantified for non-motorized mobility in arterial roads, collectors and circulation areas in parks of the lower section of the river basin, consisting mainly of cementitious base materials. The most common three types of coatings were interlocked pavements (41.47%), inloco molded concrete (21.75%), and hydraulic tile (13.57%). Such constructed areas can be adapted to compose an Urban Sustainable Drainage System, whose techniques allow the infiltration of water in the soil, reducing the interferences in the natural water cycle.